Merry wives of Maggody [large type] : an Arly Hanks mystery - Hess, Joan (Thorndike Press large print mystery, 2010)
When the winner of the local golf tournament is found dead in his awarded bass boat, Sheriff Arly Hanks has a host of jealous suspects.